ANALISIS DAYA SAING KELAPA SAWIT DI KABUPATEN PELALAWAN - DIKO SITANGGANG DIKO (UNIVERSITAS LANCANG KUNING, 2021)
Palm oil is one of the most prominent and important commodities for Pelalawan District. In Pelalawan District, Palm oil is a commodity that is one of the regions flagship commodities. Palm oil is also a producer of palm oils (CPO – Crude Palm Oil) and the core of palm oil (Palm – Keruel) which is one source of non – oil and foreign exchange producer for Indonesia. Riau Province is the province with the highest average CPO production in Indonesia, it is amounting to 8.540.182 tons or 21.47%. In 2019 the area of oil palm plantation in Riau Province is estimated at 2,8 million hectares. The results of the analysis using the Policy Analysis Matrix (PAM) method obtained that oil palm farming in Pelalawan District has a high competitiveness, (competitive advantage and comparative advantage) it is known by the value of small PCR and DRC from (one) of 0,10 and 27.